Answer:
![\frac{1}{2\sqrt{5} }](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B2%5Csqrt%7B5%7D%20%7D)
Step-by-step explanation:
Let,
= y
sin(y) = ![\frac{x}{6}](https://tex.z-dn.net/?f=%5Cfrac%7Bx%7D%7B6%7D)
![\frac{d}{dx}\text{sin(y)}=\frac{d}{dx}(\frac{x}{6})](https://tex.z-dn.net/?f=%5Cfrac%7Bd%7D%7Bdx%7D%5Ctext%7Bsin%28y%29%7D%3D%5Cfrac%7Bd%7D%7Bdx%7D%28%5Cfrac%7Bx%7D%7B6%7D%29)
![\frac{d}{dx}\text{sin(y)}=\frac{1}{6}](https://tex.z-dn.net/?f=%5Cfrac%7Bd%7D%7Bdx%7D%5Ctext%7Bsin%28y%29%7D%3D%5Cfrac%7B1%7D%7B6%7D)
---------(1)
![\frac{1}{6}=\text{cos}(y)\frac{dy}{dx}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B6%7D%3D%5Ctext%7Bcos%7D%28y%29%5Cfrac%7Bdy%7D%7Bdx%7D)
![\frac{dy}{dx}=\frac{1}{6\text{cos(y)}}](https://tex.z-dn.net/?f=%5Cfrac%7Bdy%7D%7Bdx%7D%3D%5Cfrac%7B1%7D%7B6%5Ctext%7Bcos%28y%29%7D%7D)
cos(y) = ![\sqrt{1-\text{sin}^{2}(y) }](https://tex.z-dn.net/?f=%5Csqrt%7B1-%5Ctext%7Bsin%7D%5E%7B2%7D%28y%29%20%7D)
= ![\sqrt{1-(\frac{x}{6})^2}](https://tex.z-dn.net/?f=%5Csqrt%7B1-%28%5Cfrac%7Bx%7D%7B6%7D%29%5E2%7D)
= ![\sqrt{1-(\frac{x^2}{36})}](https://tex.z-dn.net/?f=%5Csqrt%7B1-%28%5Cfrac%7Bx%5E2%7D%7B36%7D%29%7D)
Therefore, from equation (1),
![\frac{dy}{dx}=\frac{1}{6\sqrt{1-\frac{x^2}{36}}}](https://tex.z-dn.net/?f=%5Cfrac%7Bdy%7D%7Bdx%7D%3D%5Cfrac%7B1%7D%7B6%5Csqrt%7B1-%5Cfrac%7Bx%5E2%7D%7B36%7D%7D%7D)
Or ![\frac{d}{dx}[\text{sin}^{-1}(\frac{x}{6})]=\frac{1}{6\sqrt{1-\frac{x^2}{36}}}](https://tex.z-dn.net/?f=%5Cfrac%7Bd%7D%7Bdx%7D%5B%5Ctext%7Bsin%7D%5E%7B-1%7D%28%5Cfrac%7Bx%7D%7B6%7D%29%5D%3D%5Cfrac%7B1%7D%7B6%5Csqrt%7B1-%5Cfrac%7Bx%5E2%7D%7B36%7D%7D%7D)
At x = 4,
![\frac{d}{dx}[\text{sin}^{-1}(\frac{4}{6})]=\frac{1}{6\sqrt{1-\frac{4^2}{36}}}](https://tex.z-dn.net/?f=%5Cfrac%7Bd%7D%7Bdx%7D%5B%5Ctext%7Bsin%7D%5E%7B-1%7D%28%5Cfrac%7B4%7D%7B6%7D%29%5D%3D%5Cfrac%7B1%7D%7B6%5Csqrt%7B1-%5Cfrac%7B4%5E2%7D%7B36%7D%7D%7D)
![\frac{d}{dx}[\text{sin}^{-1}(\frac{2}{3})]=\frac{1}{6\sqrt{1-\frac{16}{36}}}](https://tex.z-dn.net/?f=%5Cfrac%7Bd%7D%7Bdx%7D%5B%5Ctext%7Bsin%7D%5E%7B-1%7D%28%5Cfrac%7B2%7D%7B3%7D%29%5D%3D%5Cfrac%7B1%7D%7B6%5Csqrt%7B1-%5Cfrac%7B16%7D%7B36%7D%7D%7D)
![=\frac{1}{6\sqrt{\frac{36-16}{36}}}](https://tex.z-dn.net/?f=%3D%5Cfrac%7B1%7D%7B6%5Csqrt%7B%5Cfrac%7B36-16%7D%7B36%7D%7D%7D)
![=\frac{1}{6\sqrt{\frac{20}{36} }}](https://tex.z-dn.net/?f=%3D%5Cfrac%7B1%7D%7B6%5Csqrt%7B%5Cfrac%7B20%7D%7B36%7D%20%7D%7D)
![=\frac{1}{\sqrt{20}}](https://tex.z-dn.net/?f=%3D%5Cfrac%7B1%7D%7B%5Csqrt%7B20%7D%7D)
![=\frac{1}{2\sqrt{5}}](https://tex.z-dn.net/?f=%3D%5Cfrac%7B1%7D%7B2%5Csqrt%7B5%7D%7D)
Answer:
RT-ST=QS-ST, because subtracting the same quantity from two lines that have been stated to be equal.
Therefore RS=TQ
Angle R=Angle Q, because it is an isosceles triangle
Triangle AR
S is congruent to ATQ.
AT=AS
Because TAS is isosceles, angles 5 and 6 are equal.
Therefore, angles 4 and 7 are equal, because they are supplementary angles of the same angle.
And angles 1 and 3 are equal, because the other two angles in the triangle are equal.
The triangles RAT and QAS are congruent with SAS.
Step-by-step explanation: Can u gimme brain plz!
230 divided by 12 1/2 is 18.4. 18.4 times the width is 230. so the length is 18.4.
Answer:
m= -16
Step-by-step explanation:
m/4+3= -1
-3 -3
m/4= -4
*4 *4
m= -16